Corporate real estate management in Singapore: A business management perspective - Tay, Linda; Liow, Kim Hiang (International Journal of Strategic Property Management, 2010)
Corporate real estate management (CREM) practices in Asia have been a relatively under‐researched area compared with those from Europe and North America. This paper represents an attempt to enhance the current knowledge of CREM in Asia. Part I of this study provides a snapshot of CREM practices among Singapore multi‐national companies (MNCs) and listed firms. Ninety‐seven firms were surveyed on three main business management perspectives: corporate real estate planning, corporate real estate organizational structure and corporate real estate performance. The study found that in general, corporate real estate (CRE) is under‐managed among MNCs and listed firms in Singapore. Creating awareness of the importance and relevance of good CREM practices is therefore the most pertinent task. Part II of this paper focuses specifically on CRE performance. A data‐driven analytical technique is adopted to study the direct and indirect effects of performance factors on corporate real estate. The results indicate that only corporate real estate planning and the existence of a real estate unit have a direct impact on corporate real estate performance. This finding is both theoretically expected and important. The results reinforces current literature postulations on the importance of strategic planning as the key skills that corporate real estate managers need to be equipped with to meet the challenges ahead.First Published Online: 18 Oct 2010